Calcifying fibrous tumor of stomach: a rare case report of an upper gastrointestinal bleeding - Ye, BaoLong; Chen, ZiWen; Xie, JunFeng; Xi, KeXing; Zeng, Xin; Zhong, CaiLiang (Frontiers in Oncology, 2025)
IntroductionCalcifying fibrous tumor (CFT) is an uncommon benign fibrous neoplastic lesion that may manifest as singular or multiple tumors and usually occurs in children or young adults. CFT originates in the muscularis propria of the stomach and is a very rare disease. Here, we report a case of gastric CFT with upper gastrointestinal bleeding.Case informationA 39-year-old male was urgently referred to our hospital with haematemesis and melena that had developed over the course of 2 hours. Enhanced abdominal CT imaging revealed a nodular lesion, measuring approximately 3.2 × 2.1 × 1.6 cm, protruding from the posterior wall of the gastric body into the gastric lumen. The lesion exhibited scattered calcifications, smooth margins, and a CT attenuation value of 50 Hounsfield units (HU). Gastroscopic ultrasonography performed in the gastroenterology department revealed a semicircular submucosal mass with signs of active bleeding. Initially, the tumor was diagnosed as a gastrointestinal stromal tumor (GIST), and surgical intervention was undertaken due to ongoing hemorrhage. Postoperative histopathological examination confirmed the diagnosis of a gastric calcifying fibrous tumor (CFT).ConclusionCFT originating from the muscularis propria of the stomach is exceptionally rare, and the case presented here mimicked a gastric submucosal tumor (SMTs),clinicians should consider this differentia diagnosis when evaluating patients with suspected cases.